2020
DOI: 10.18231/j.ijmr.2020.063
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasites in pregnant women

Abstract: Parasitic infections affect tens of millions of pregnant women worldwide, and directly or indirectly lead to a spectrum of adverse maternal and fetal/placental effects. To determine the prevalence of intestinal parasites in pregnant women and its association with various factors. Stool specimens were collected from pregnant women in a clean, wide mouth, leak-proof screw capped container. Formol ether Concentration technique was performed to increase the yield of the eggs and larvae. Modified Acid Fast staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(44 reference statements)
6
0
0
Order By: Relevance
“…Our study revealed the highest rates of IPIs among primigravida women (41.6%) followed by those who were bigravidae (31.1%) and multigravidae (29.4%). This is in concordance with the findings of Adedojo et al [ 35 ] in Nigeria and Paranjpe et al [ 36 ] in India. It was also shown that the odds of being infected by IPIs were increased by about 2 times among primigravida women than those who were pregnant for multiple times.…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed the highest rates of IPIs among primigravida women (41.6%) followed by those who were bigravidae (31.1%) and multigravidae (29.4%). This is in concordance with the findings of Adedojo et al [ 35 ] in Nigeria and Paranjpe et al [ 36 ] in India. It was also shown that the odds of being infected by IPIs were increased by about 2 times among primigravida women than those who were pregnant for multiple times.…”
Section: Discussionsupporting
confidence: 93%
“…The pooled prevalence of intestinal parasites among pregnant women in this systematic review and metaanalysis was 38.54 (28.77, 48.32). This is similar to findings of the studies conducted in India (42.67%) [25], Ghana (30.5%) [26], Ibadan Nigeria (43.4%) [27], Colombia (41%) [28], Southeast Nigeria (32.4%) [29], Tribhuvan University teaching hospital, Nepal (35%) [8], Ram Janaki Hospital, Janakpurdham, Nepal (42%) [30], and Cameroon (47.1%) [31]. The pooled prevalence in this study is lower than studies conducted in the Caribbean (66.2%) [32], Venezuela (73.9%) [33], Thai Burmese border, Southeast Asia (70%) [34], Guinea (81%) [35], Sub-Saharan Africa (66%) [36] and Indonesia (67.7%) [37].…”
Section: Discussionsupporting
confidence: 92%
“…Pregnant women who have no latrine were 2.94 times more likely to have intestinal parasites compared to women who have a latrine. This is in line with studies conducted in a tertiary multispecialty teaching hospital in Mumbai, India [25], Kasoa Polyclinic, Ghana, in which pregnant women who shared a toilet facility had 2.78-fold greater odds of intestinal parasite infections compared to those who owned a toilet facility [38], and Abeokuta, Nigeria [39]. This may be because, in the absence of latrine, there is open defecation, which can contaminate food and water that pregnant women consume, and finally, predispose them to intestinal parasites.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations